BIOCAMP NA ÓTICA PEDAGÓGICA: UM RELATO DE EXPERIÊNCIA - Bastos, Roberto Mamedio (South American Journal of Basic Education, Technical and Technological, 2016)
Abstract: BIOCAMP is an extension project presented as a pedagogical proposal of inclusion of high school students in scientific research universe. This is a field activity carried out in the Experimental Field of Federal University of Acre – Catuaba Farm. This work presents an overview of the educational experiences of students and teachers during the development of this project. In a pedagogical and hermeneutics perspective, we report how such activities enrich and promote the production of teaching knowledge and the learning of the students, by bringing together theory and practice. The results reinforce the need and importance of school activities of surpassing the school environment, as a condition for a more meaningful learning. KEYWORDS: Education, reflection, theory and practice